Long-term Outcomes of Tibial Spine Avulsion Fractures After Open Reduction With Osteosuturing Versus Arthroscopic Screw Fixation: A Multicenter Comparative Study - Jääskelä Maija; Turati Marco; Lempainen Lasse; Bremond Nicolas; Courvoisier Aurelien; Henri Antoine; Accadbled Franck; Sinikumpu Jaakko (SAGE PUBLICATIONS INC, 2025)
Background: More information is needed regarding return to preinjury sport levels and patient-reported outcomes after tibial spine avulsion (TSA) fracture, which is most common in children aged 8 to 12 years.
Purpose: To analyze return to play/sport (RTP), subjective knee-specific recovery, and quality of life in patients after TSA fracture treated with open reduction with osteosuturing versus arthroscopic reduction with internal screw fixation.
Study Design: Cohort study; Level of evidence, 3.
Methods: This study included 61 patients <16 years old with TSA fracture treated via open reduction with osteosuturing (n = 32) or arthroscopic reduction with screw fixation (n = 29) at 4 institutions between 2000 and 2018; all patients had at least 24 months of follow-up (mean ± SD, 87.0 ± 47.1 months; range, 24-189 months). The patients completed questionnaires regarding ability to return to preinjury-level sports, subjective knee-specific recovery, and health-related quality of life, and results were compared between treatment groups. Univariate and multivariate logistic regression analyses were conducted to determine variables associated with failure to return to preinjury level of sport.
Results: The mean patient age was 11 years, with a slight male predominance (57%). Open reduction with osteosuturing was associated with a quicker RTP time than arthroscopy with screw implantation (median, 8.0 vs 21.0 weeks; P < .001). Open reduction with osteosuturing was also associated with a lower risk of failure to RTP at preinjury level (adjusted odds ratio, 6.4; 95% CI, 1.1-36.0; P = .035). Postoperative displacement >3 mm increased the risk of failure to RTP at preinjury level regardless of treatment group (adjusted odds ratio, 15.2; 95% CI, 1.2-194.9; P = .037). There was no difference in knee-specific recovery or quality of life between the treatment groups.
Conclusion: Open surgery with osteosuturing was a more viable option for treating TSA fractures because it resulted in a quicker RTP time and a lower rate of failure to RTP as compared with arthroscopic screw fixation. Precise reduction contributed to improved RTP.